Motivasi Belajar Peserta Didik Ditinjau Dari Model Pembelajaran DiSTAD - Ana Silfiani Rahmawati; Danar Wulan (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
This study aims to find out the student learning motivation in terms of DiSTAD learning model. This study is a quantitative research using a quasi experimental design. The population in this research were all VIII grade students of Satap Pong Meleng Manggarai Junior High School which consisted of two class. The sample taken by sampling saturated, because all population were taken (summary not exceed 30 people per class. ÃÂ The data analysis used the descriptive analysis and inferensial analysis. The results show that: the implementation of DiSTAD learning model gives a significantly positive effect to the student learning motivation, and it is shown by the output value of the t-test (5,531) at the significance level of 0.00 (significance < 0.05).